Velocity estimation in ultrasound images: A block matching approach - Boukerroui, D; Noble, J; Brady, M (2003)
In this paper, we focus on velocity estimation in ultrasound images sequences. Ultrasound images present many difficulties in image processing because of the typically high level of noise found in them. Recently, Cohen and Dinstein have derived a new similarity measure, according to a simplified image formation model of ultrasound images, optimal in the maximum likelihood sense. This similarity measure is better for ultrasound images than others such as the sum-of-square differences or normalised cross-correlation because it takes into account the fact that the noise in an ultrasound image is multiplicative Rayleigh noise, and that displayed ultrasound images are log-compressed. In this work we investigate the use of this similarity measure in a block matching method. The underlying framework of the method is Singh's algorithm. New improvements are made both on the similarity measure and the Singh algorithm to provide better velocity estimates. A global optimisation scheme for algorithm parameter estimation is also proposed. We show that this optimisation makes an improvement of approximately 35% in comparison to the result obtained with the worst parameter set. Results on clinically acquired cardiac and breast ultrasound sequences, demonstrate the robustness of the method. © Springer-Verlag Berlin Heidelberg 2003.